Biochemical Evaluation of Some Liver Enzymes in Type 2 Diabetes Mellitus Iraqi Patients - Ali Abdul Hussain Kasim; Mohammed M. Mohammed (College of Pharmacy / Mustansiriyah University, 2012)
Liver is the main organ of glucose storage as glycogen and metabolism. This key function of liver exposes it to many types of diseases with metabolic disorders, particularly diabetes. Many studies had showed that; diabetes is associated with high risk of chronic liver disease, primary liver cancers and liver cirrhosis. However, most of these studies were performed in Western countries, and there is a lack of information from Iraq. The aim of the study is to evaluate some hepatic enzymes in Iraqi patients with chronic type 2 diabetes mellitus (T2DM) compared with healthy volunteers. Sixty Iraqi subjects with type 2 DM, and sixty healthy volunteers as control group were included in this study. The levels of (Glucose, ALT, AST, GGT, and ALP) were measured. The mean values of concentration levels of ALT, AST and GGT were significantly higher in T2DM than the control group (P≤ 0.001 for ALT, GGT and P≤ 0.05 for AST). In contrast, there is no significant difference in ALP levels in the two study groups. The results of this study are in accordance with previously reported high prevalence rates of abnormal liver enzymes in patients with type 2 diabetes mellitus in other populations.